(untitled) (Research, Society and Development, 2021)
This article is a review of bibliography carried out with the objective of compiling and analyzing existing information on the use of ozone in the prevention and therapy of mastitis in dairy cows, and thus to know the fundamentals of the use of ozone within livestock and the potential that this treatment may face the battle against microbial resistance that is currently growing stronger. The methodology used was by searching in different databases such as Capes, Dialnet, Google Scholar, Scielo, LILACS, Spacenet, choosing articles and documents specifically focused on the use of ozone in agriculture and livestock, as well as its discovery and development. The search resulted in a wealth of very varied information on the use of ozone in livestock, giving a perspective on how ozone therapy is being used and its possible future uses. At the end of this review it was concluded that although it is true there is much information on the use of ozone in mastitis in dairy cows, even the diversity of this information is not abundant, limiting itself to the use of ozone in therapeutics and leaving on a little side the prevention, in addition to this, there is also a deficit of information on dosages and means of application, so future research is suggested to strengthen information on these points and practically reinforce the information that is already theoretically available.